(untitled) (VERUM: Journal of Scientific Initiation, 2023)
This study aims to present the profile of students assisted by the student assistance programs at the Federal University of Uberlândia (UFU), based on data collected by the social work team during the implementation of the Proae Assistance 04/2021 Notice, an instrument that facilitates access to the Student Assistance Policy benefits at the institution. Understanding the profile of public policy beneficiaries is of fundamental importance for the creation, evaluation, and reformulation of related programs, in this case, the National Student Assistance Program (PNAES), based on the reality of the target audience of these actions. Based on the data, the thesis is supported that the students applying for assistance have a profile that requires qualified support during their academic training. From a comprehensive analysis, it is necessary that the concept of student assistance goes beyond priority assistance, with expanded budgeting/financing to cover all ten areas outlined by PNAES, and act in coordination with other university sectors.